2018
DOI: 10.2147/ijn.s156984
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of a Pt-loaded nanocomposite based on graphene quantum dots combats hypoxia-induced chemoresistance of oral squamous cell carcinoma

Abstract: Background Tumor microenvironment plays an important role in the chemoresistance of oral squamous cell carcinoma (OSCC). Hypoxia in the microenvironment is one of the important factors that contributes to OSCC chemoresistance; therefore overcoming hypoxia-mediated chemoresistance is one of the great challenges in clinical practice. Methods In this study, we developed a drug delivery system based on Pt-loaded, polyethylene glycol-modified graphene quantum dots via chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…To overcome the hypoxia-induced resistance to chemotherapy in the tumor microenvironment, Wei et al [189] established a DDRS based on Pt and polyethylene glycol-GQDs. First, GQDs were synthesized by chemical oxidation of dried CX-7 carbon black with HNO 3 .…”
Section: Epr-ph Delivery-release Modementioning
confidence: 99%
See 3 more Smart Citations
“…To overcome the hypoxia-induced resistance to chemotherapy in the tumor microenvironment, Wei et al [189] established a DDRS based on Pt and polyethylene glycol-GQDs. First, GQDs were synthesized by chemical oxidation of dried CX-7 carbon black with HNO 3 .…”
Section: Epr-ph Delivery-release Modementioning
confidence: 99%
“…13 Schematic illustration of a multifunctional platform for anticancer therapy with high efficacy against hypoxia-induced chemoresistance of OSCC (reprinted/reproduced with the permission of Ref. [ 189 ], (reprinted/reproduced with the permission of Ref. [ 189 ], copyright 2018, Int J Nanomedicine) …”
Section: Applications Of Gqds In Drug Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…PtNPs induced apoptosis in Raw 264.7 cells by altering cell morphology and density and also increased apoptosis, activation of caspases 3 and 7, and DNA fragmentation [216]. Wei et al [217] reported that polyethylene glycol-graphene quantum dots-Pt (GPt) with an average size of 5 nm sensitize oral squamous cell carcinoma (OSCC) in both normoxic and hypoxic conditions. GPt exhibits a strong inhibitory effect on tumor growth with less systemic drug toxicity and helps in combating hypoxia-induced chemoresistance in an OSCC xenograft mouse tumor model.…”
Section: Cytotoxicity Of Ptnps In Cancer and Non-cancer Cellsmentioning
confidence: 99%